The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1600-0781.2008.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultraviolet B‐induced vitamin D levels on host resistance to Mycobacterium tuberculosis: a pilot study in immigrant Asian adults living in the United Kingdom

Abstract: Asian immigrants to the United Kingdom demonstrate much higher tuberculosis rates than the indigenous population. This is postulated to be because of their low vitamin D levels, consequent upon a combination of diet and their reduced ultraviolet (UV) exposure in the United Kingdom, because vitamin D enhances antimycobacterial activity in in vitro systems. The aim of this study was to examine the relationship between UVB exposure, vitamin D levels and tuberculo-immunity in Asian immigrants in the United Kingdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…According to this measure, vitamin D supplementation suppressed bacterial growth at 24 h, an indicator of innate immunity, by 20.4% more than placebo (P = 0.03) but did not affect luminescence or interferon-g secretion at 96 h-an indicator of acquired immunity. On the other hand, in a study by Yesudian et al (30), significant change in antimycobacterial immunity (as expressed by the BCG-lux assay) did not occur even though the mean 25(OH)D concentration increased significantly after ultraviolet B treatment (P , 0.01).…”
Section: Discussionmentioning
confidence: 93%
“…According to this measure, vitamin D supplementation suppressed bacterial growth at 24 h, an indicator of innate immunity, by 20.4% more than placebo (P = 0.03) but did not affect luminescence or interferon-g secretion at 96 h-an indicator of acquired immunity. On the other hand, in a study by Yesudian et al (30), significant change in antimycobacterial immunity (as expressed by the BCG-lux assay) did not occur even though the mean 25(OH)D concentration increased significantly after ultraviolet B treatment (P , 0.01).…”
Section: Discussionmentioning
confidence: 93%
“…Although there is some evidence that raising 25‐D levels fuels innate immune function by increasing the availability of precursor 25‐D to be converted to 1,25‐D, 10,33 the results are not consistent, 34 and further studies are needed. Even if this were to be confirmed in the healthy general population, however, it would not necessarily be true for those who already have bacteria‐induced VDR dysfunction.…”
Section: Vitamin D Metabolites Vitamin D Receptor Dysfunction and Tmentioning
confidence: 96%
“…[1][2][3][4][5][6][7][8] However, other studies have shown a deleterious or no beneficial effect of vitamin D supplementation on certain diseases. [9][10][11][12][13][14][15][16][17][18] The effects of vitamin D are the result of genomic and nongenomic actions mediated by the active form of vitamin D, termed calcitriol, which is also known as 1,25-dihydroxyvitamin D3 (1,25-D). Yet most of the studies evaluating vitamin D and its association with disease are based on 25-hydroxyvitamin D (25-D) serum levels and not 1,25-D.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in the role of vitamin D deficiency in a number of chronic health problems, including autoimmune diseases 1–8 . However, other studies have shown a deleterious or no beneficial effect of vitamin D supplementation on certain diseases 9–18 . The effects of vitamin D are the result of genomic and non‐genomic actions mediated by the active form of vitamin D, termed calcitriol, which is also known as 1,25‐dihydroxyvitamin D3 (1,25‐D).…”
Section: Introductionmentioning
confidence: 99%